A parallel architecture for data compression - Henriques, S.; Ranganathan, N. (Parallel and Distributed Processing, 2nd IEEE Symposium On, 1990)
The authors describe a parallel algorithm and architecture for implementing the LZ technique for data compression. Data compression is the reduction of redundancy in data representation in order to decrease storage and communication costs. The LZ-based compression method is a very powerful technique and gives very high compression efficiency for text as well as image data. The proposed architecture is systolic and uses the principles of pipelining and parallelism in order to obtain high speed and throughput. The order of complexity of the computations is reduced from n/sup 2/ to n. The data compression hardware can be integrated into real time systems so that data can be compressed and decompressed on-the-fly. The basic processor cell for the systolic array is currently being implemented using CMOS VLSI technology.< >